A consensus on best R&D practices Derek L. Ransey and Jay L. Rogers extract seven "best practices" from studies by four consultants - Ransley, Derek L. and Jay L. Rogers (Research management (Now: research technology management))
Four studies agree on seven priorities, beginning with alignment of technology strategy with the corporate and business strategy